2020
DOI: 10.1038/s41431-020-00738-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of best practices for return of results in an international survey of psychiatric genetics researchers

Abstract: Many research sponsors and genetic researchers agree that some medically relevant genetic findings should be offered to participants. The scarcity of research specific to returning genetic results related to psychiatric disorders hinders the ability to develop ethically justified and empirically informed guidelines for responsible return of results for these conditions. We surveyed 407 psychiatric genetics researchers from 39 countries to examine their perceptions of challenges to returning individual results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…However, despite these favourable views, others raised concerns about the uncertainty of the information being returned to participants [ 137 , 140 ], the potential impact on scientific progress [ 140 ], burden on researchers who cannot provide the necessary support [ 136 ] or lack of infrastructure and resources [ 143 ], and blurring lines between research and clinical care [ 136 , 140 ]. Others held concerns for participants’ privacy and confidentiality [ 128 , 137 ], discrimination from insurance companies and banks [ 143 ], their ability to retain control of their data [ 137 ] and ensuring informed consent [ 18 , 137 ]. In addition, researchers were worried about the potential for adverse psychological reactions from returning results, including worry [ 136 ], confusion [ 136 , 137 ], anxiety, guilt [ 137 ], and stigmatization [ 137 ].…”
Section: Views On Return Of Study-specific Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite these favourable views, others raised concerns about the uncertainty of the information being returned to participants [ 137 , 140 ], the potential impact on scientific progress [ 140 ], burden on researchers who cannot provide the necessary support [ 136 ] or lack of infrastructure and resources [ 143 ], and blurring lines between research and clinical care [ 136 , 140 ]. Others held concerns for participants’ privacy and confidentiality [ 128 , 137 ], discrimination from insurance companies and banks [ 143 ], their ability to retain control of their data [ 137 ] and ensuring informed consent [ 18 , 137 ]. In addition, researchers were worried about the potential for adverse psychological reactions from returning results, including worry [ 136 ], confusion [ 136 , 137 ], anxiety, guilt [ 137 ], and stigmatization [ 137 ].…”
Section: Views On Return Of Study-specific Resultsmentioning
confidence: 99%
“…Clinical research setting. Seventeen studies have investigated views of researchers on returning IRR [44,76,84,119,18,128,[133][134][135][136][137][138][139][140][141][142][143]. A study of 39 psychiatric genetic researchers from 17 countries indicated that the majority of participants were either not returning results at all or had returned results but were not doing so in a systematic way [137].…”
Section: Researchers' Views On Returning Study-specific Resultsmentioning
confidence: 99%
“…All stakeholders prioritised RoR that could lead to surveillance, prevention and/or treatment. Professionals raised concerns, including difficulties obtaining informed consent, lack of time and resources, possible overdiagnosis, clinical follow-up, and potential for psychological harm [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…All stakeholders prioritised RoR that could lead to surveillance, prevention and/or treatment. Professionals raised concerns, including di culties obtaining informed consent, lack of time and resources, possible overdiagnosis, clinical follow-up, and potential for psychological harm [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%